FOOD SPOILAGE MITIGATION THROUGH MODERN PROCESSING TECHNOLOGIES - P Aileen Sonia Dhas; Monish Raj R; Kiran Kumar S; S B Chandra Lekha; Sindhu D (The Bioscan, 2025)
Food spoilage is a critical issue affecting food security, public health, and the global economy. Spoilage, which results from microbial activity, enzymatic degradation, oxidation, and improper storage conditions, leads to significant quality deterioration and food waste. According to the Food and Agriculture Organization (FAO), approximately one-third of all food produced globally is lost or wasted, much of it due to spoilage. This has catalysed a growing demand for innovative and sustainable food preservation and spoilage detection technologies. Traditional methods such as refrigeration, chemical preservatives, and thermal processing have been widely used to extend shelf life. However, these approaches often have limitations, including nutrient degradation, changes in sensory attributes, and consumer concerns over synthetic additives